Magnesium concentration in medicinal products using the fully controlled inkjet approach. - Mkashaf, Ihsan A. (Journal of Basrah Researches (Sciences), 2024)
The measurement of magnesium ion in homemade ph samples has been designed using a fully automated microfluidic device. This study involved the design of two channel microchips (45 × 3 cm). Arduino mega microcontrollers were used to operate the suggested system. The DIY micro-peristaltic pumping was operated by the first type that was used for remove specimens and chemical agents extracted from the microchip and transfer them to the UV. Visible spect. We are use the apparatus a 7-microliter flow cell in our lab, also the second type called mega, was employed as logger’s data to alter, it was received and record the outcomes since highest point corresponding to concentrations using an Office Excel 2016 application. A correlation coefficient (R2) 0.9997 and the linearity varied from 0.5 to 10 µg/mL. Ten measurements of Mg ion 8 µg/mL had a relative standard deviation of (0.872%).